2013
DOI: 10.1038/pr.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent maternal hypoxia has an influence on regional expression of endothelial nitric oxide synthase in fetal arteries of rabbits

Abstract: Background: Maternal hypoxia induces sustained fetal adaptations associated with changes in gene expression. We hypothesized that intermittent maternal hypoxia has an influence on regional expression of endothelial nitric oxide synthase (eNOS) in fetal arteries of New Zealand White rabbits. Methods: Timed-pregnant New Zealand White rabbits (term = 30 ± 1 d) were randomly assigned to a normoxic control group (n = 5) or a hypoxia group (12% O 2 , n = 5) during days 10-29 of pregnancy. At the end of pregnancy (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Indeed, in skin biopsies, it has been reported an increase in eNOS mRNA expression in severely hypoxemic OSA patients 16 . At the vascular level, an increase of eNOS expression and activity has been described in carotid arteries from fetal rabbits exposed to IH 22 . Also, in hypertensive rats, IH induced formation of available NO stores and enhanced the capacity of aortic rings to store NO improving endothelial function 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in skin biopsies, it has been reported an increase in eNOS mRNA expression in severely hypoxemic OSA patients 16 . At the vascular level, an increase of eNOS expression and activity has been described in carotid arteries from fetal rabbits exposed to IH 22 . Also, in hypertensive rats, IH induced formation of available NO stores and enhanced the capacity of aortic rings to store NO improving endothelial function 23 .…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of hypoxia on the expression of eNOS are contradictory. Some studies show increased eNOS in the carotid artery and decreased in the femoral artery [ 57 ] at the protein and gene expression levels [ 59 ]. In the heart, eNOS expression was increased at the protein and decreased at the gene expression level [ 85 ].…”
Section: Prenatal Hypoxiamentioning
confidence: 99%
“…Under normoxia, HIF-1α is rapidly degraded, but if the partial pressure of oxygen decreases, it is stabilized and accumulates in the cells. HIF-1α maintains oxygen homeostasis by regulating the expression of hundreds of genes and interacts with pathways involved in the regulation of the cardiovascular system, such as the chemoreflex, sympathetic drive [ 54 ], renin-angiotensin-aldosterone system (RAAS) [ 55 , 56 ], and local vessel wall components such as nitric oxide (NO) [ 57 , 58 , 59 ] and endothelin-1 [ 60 , 61 ]. Moreover, HIF directly interacts with the circadian clock because HIF-1α controls the expression of several canonical circadian genes and the response to hypoxia is gated by the circadian clock [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a few studies, however, the opposite has been observed. For instance, in mesenteric and carotid arteries of protein restricted or hypoxic models, eNOS expression has been shown to be increased (71,328). Corresponding to the majority of evidence for reduced eNOS expression or activity, NO-mediated mesenteric artery vasodilation (265,266) , BH 4 is oxidized to the BH 3 · radical and then to BH 2 reducing its availability to eNOS.…”
Section: Vasodilator Mechanismsmentioning
confidence: 99%